2010
DOI: 10.1002/lapl.201010074
|View full text |Cite
|
Sign up to set email alerts
|

High power diode-pumped continuous wave and Q-switch operation of Tm,Ho:YVO4 laser

Abstract: High power diode-pumped continuous wave (CW) and Q-switch operation of Tm,Ho:YVO4 laser is reported. Using two Tm,Ho:YVO 4 rods in a single cavity, up to 20.2 W of CW output lasing at 2054.7 nm was obtained under cryogenic temperature of 77 K with an optical to optical conversion efficiency of 32.9%. For Q-switch operation, up to 19.4 W of output was obtained under 15 kHz pulse repetition frequency (PRF) with a minimum pulse width of 24.2 ns. In addition, different pulse repetition frequencies of Q-switch oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…[33][34][35][36]. Roomtemperature AOM Q-switched Tm,Ho:YLF lasers were also reported, however, with much worse output characteristics [37].…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35][36]. Roomtemperature AOM Q-switched Tm,Ho:YLF lasers were also reported, however, with much worse output characteristics [37].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the cross-relaxation processes in the TmTm system ( 3 H 4 þ 3 H 6 -3 F 4 þ 3 F 4 ) and following energy transfer in the Tm-Ho system ( 3 F 4 -5 I 7 ) [3], a maximal pump quantum efficiency could be expected. And many previous studies have been reported for generating 2.0 μm laser radiation by using Tm/Ho co-doped YAG [4], YLF [5], YVO 4 [6], and YAP [5].…”
Section: Introductionmentioning
confidence: 98%
“…Using rare earth ion thulium (Tm 3+ ) or holmium (Ho 3+ ) as an active ion, laser operation near the 2 µm wavelength range can be obtained [1][2][3][4][5]. In past years, several diode pumped single frequency lasers based on Tm or Tm-Ho ions hosted in garnet and fluoride crystals, with emission wavelengths at 2 µm have been demonstrated [6][7][8][9][10][11][12][13][14]. Thus single frequency 2 µm lasers are attractive for coherent Doppler Lidar, Dop pler velocimetry and wind measurement.…”
Section: Introductionmentioning
confidence: 99%